2009
DOI: 10.3415/vcot-08-10-0100
|View full text |Cite
|
Sign up to set email alerts
|

Feline shoulder arthroscopy using a caudolateral portal, a cadaveric study

Abstract: The aim of this cadaveric study was to determine the normal arthroscopic anatomy of the feline shoulder from a caudolateral arthroscope portal, to compare this with the gross anatomy evident upon dissection, and to determine the degree of iatrogenic trauma caused by the arthroscopy. A 1.9 mm, 30 degrees fore oblique arthroscope via a caudolateral portal, and a 21-gauge needle via a craniolateral egress portal were used to assess intra-articular structures in eight feline cadaveric shoulders. The medial glenohu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…5 8 9 Despite shoulder arthroscopy being the gold standard diagnostic procedure for shoulder pathology, this would be unlikely to provide any further information to the case due to inability to directly observe the transverse humeral ligament. 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 8 9 Despite shoulder arthroscopy being the gold standard diagnostic procedure for shoulder pathology, this would be unlikely to provide any further information to the case due to inability to directly observe the transverse humeral ligament. 2…”
Section: Discussionmentioning
confidence: 99%
“…The transverse humeral ligament (retinaculum) runs from the lesser to the greater tubercle of the humerus, preventing luxation of the biceps tendon from the intertubercular groove, and it is a well-known anatomical structure in the dog and cat. 1 2 Gleason and colleagues 3 concluded that in humans this structure was not an actual ligament, but rather a sling formed mainly by fibres of the subscapularis tendon, with contributions from the supraspinatus tendon and the coracohumeral ligament. Complete ossification of the transverse humeral ligament was described in a human cadaveric study in only one specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic surgery can offer multiple advantages over open surgery, including improved visualization of intra-articular structures, [6][7][8] decreased surgical morbidity, and decreased postoperative pain. [9][10][11] The use of arthroscopy for diagnosis or treatment of intra-articular pathology has been reported in feline elbow, 12 shoulder, 13 and stifle joints 14 but a technique for arthroscopic examination of the feline hip joint has yet to be described.…”
Section: Introductionmentioning
confidence: 99%